Menopausal Symptoms, Postural Balance, and Functional Mobility in Middle-Aged Postmenopausal Women - João Espírito Santo; Agustín Aibar-Almazán; Antonio Martínez-Amat; Nuno Eduardo Marques de Loureiro; Vânia Brandão-Loureiro; María Leyre Lavilla-Lerma; Fidel Hita-Contreras (Diagnostics, 2021)
The aim of the present study was to determine the associations between the severity of the menopausal symptoms and postural balance and functional mobility in middle-aged postmenopausal women. A cross-sectional study was performed (171 participants, 57.18 ± 4.68 years). Severity of the menopausal symptoms (on the Menopause Rating Scale), postural balance (stabilometric platform) with eyes open and closed, and functional mobility (timed up and go test) were determined. A multivariate linear regression was performed, with body mass index, waist to hip ratio, age and fall history as possible confounders. Our findings showed that a greater severity of the menopausal symptoms at a psychological level was associated, under both eyes open and closed conditions, with worse postural control assessed by the length of the stabilogram (adjusted R2 = 0.093 and 0.91, respectively), the anteroposterior center of pressure displacements (adjusted R2 = 0.051 and 0.031, respectively) and the center of pressure velocity (adjusted R2 = 0.065 for both conditions). Older age was related to greater mediolateral displacements of the center of pressure with eyes open and closed (adjusted R2 = 0.45 and 0.58, respectively). There were no associations between the menopausal symptoms’ severity and functional mobility. We can conclude that a greater severity of psychological menopausal symptoms was independently associated with worse postural balance in middle-aged postmenopausal women.